ANALISIS PEMEROLEHAN BAHASA (LANGUAGE ACQUISITION) PADA ANAK USIA DINI RENTANG USIA 4-5 TAHUN DI PAUD INSANI KOTA MEDAN - Sarah Nasution; Asrindah Asrindah (BAHAS, 2021)
Abstract  The purpose of this study was to determine how language acquisition in early childhood aged 4-5 years in PAUD INSANI Medan City. Due to the Covid-19 pandemic and large-scale social restrictions, early childhood did not socialize with friends at school so that the vocabulary acquired by children was not as large as usual due to minimal interaction. This research is a qualitative descriptive research where the sample is preschool students. Data collection techniques were carried out by observation and interviews. From this research, it was found that early childhood can say the name according to the picture given, but their knowledge of English is still very minimal. In this study, the author tried to give a picture card of animals and fruits in two languages, when the sample was mentioned, the sample could mention it but the letter [r] could not say it perfectly. The remaining 80% of respondents can acquire the spoken languageKeywords: Early Childhood, Language Acquisition, Covid-19 Pandemic